Selection of surfactant compounds to enhance the dispersion of Beauveria bassiana - Santos, P. de S. [UNESP]; da Silva, M. A. Q.; Monteiro, A. C. [UNESP]; Gava, C. A. T. (Taylor & Francis Ltd, 2012)
This study aimed to select surfactant compounds to improve the dispersion of emulsifiable conidial suspensions of Beauveria bassiana for field application while maintaining high conidia viability. Surfactant compatibility was initially evaluated by colony growth in culture media amended with increasing doses of surfactants. In a second experiment, the conidia germination rate was evaluated after temporary exposure to the compounds under laboratory conditions. The effect of the hydrophilic-lipophilic balance (HLB) of the surfactants on conidia dispersion and viability was assessed using mixtures of the most compatible products and concentration initially selected. Unitol L/20 and Ultranex NP/100 did not show deleterious effect on colony growth on culture media, while Surfom 3409 strongly inhibited conidial germination. Unitol L/20, Ultranex NP/100 and Ultratan D did not interfere in the germination of conidia during the first 10 minutes of exposure. After 120 minutes, germination was greatly reduced at a 0.5% concentration, with the exception of Ultranex NP/100. The higher conidial dispersion and germination were obtained with HLB values between 8 and 12 and lower remaining clusters at HLB 10. Moreover, there was no significant effect of HLB values on insect mortality. Unitol L/20 and Ultranex NP/100 were the most compatible surfactants in concentrations lower than 0.5%. The HLB value selected for dispersion of B. bassiana on water based formulations was 10.
Keywords: Biological control; conidial dispersion; hydrophilic-lipophilic balance value; formulation